Jurnal akuntansi & auditing Indonesia: A LEARNING OF NEW ZEALAND: A STEP TOWARD GOOD GOVERNANCE FOR INDONESIA - Indra Bastian (akuntansi UII, 2011)
A number of public finance management reforms over the last several decades have served to improve governance in Indonesia. In too many cases, however, reform measures have failed to realize their full potential. Certainly the need for fundamental change was widely accepted.